Tariff systems for fleets of vehicles: a study on the portfolio of Fidelidade - Centeno, M. de Lourdes (2022)
In Portugal, insurance policies for fleets of vehicles are, in general, similar to policies for individual vehicles. Such is the case of the insurance company at hand. The experience rating system is practically the same as in individual motor insurance and is applied independently to each vehicle, thus having no effect on the premium paid by other vehicles in the fleet. This experience rating system is inefficient since it ignores the potential fleet-specific risks in the a posteriori tariff. We considered two credibility-based experience rating schemes proposed by Desjardins, Dionne and Pinquet in 2001. One is based on the claims numbers at fleet level and the other is based on the claims numbers at vehicle level. We applied both models in order to calculate experience rating coefficients for the vehicles in the portfolio of fleets of the insurer. We propose different estimators for the structure parameters of the model, which in our opinion handle better the heterogeneity of the time exposures of our data set. Keywords.